Preparing a workforce for the new blue economy : people, products and policies - Hotaling, Liesl; Spinrad, Richard W.; Head, Martin Koehring (Elsevier, 2021)
Preparing a Workforce for the New Blue Economy: People, Products and Policies discusses the Blue Economy, how the industry will develop, and how to train the next generation. The book considers the use of big data, key skillsets, training undergraduate and graduate students, the Transition Assistance Program (TAP) in the US, economic opportunities in African coastal countries, and governmental agencies, non-profits and NGO's. Finally, a broad range of case studies are provided, covering oil spills, commercial fishing, data protection and harvesting, sustainability and weather forecasting, all presented to highlight the educational requirements of the workforce and potential economic opportunities.